2013
DOI: 10.3174/ajnr.a3529
|View full text |Cite
|
Sign up to set email alerts
|

4D Digital Subtraction Angiography: Implementation and Demonstration of Feasibility

Abstract: BACKGROUND AND PURPOSE: Conventional 3D-DSA volumes are reconstructed from a series of projections containing temporal information. It was our purpose to develop a technique which would generate fully time-resolved 3D-DSA vascular volumes having better spatial and temporal resolution than that which is available with CT or MR angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 12 publications
0
78
0
1
Order By: Relevance
“…1 In this small study, we have shown that for the evaluation of the extracranial canine vasculature, 4D DSA frequently provided information that 2 experienced observers preferred over that provided by 2D or 3D studies. Although we did not explicitly ask whether the 4D dataset contained information equivalent to that in the combination of 2D and 3D series, we believe that this may be the case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In this small study, we have shown that for the evaluation of the extracranial canine vasculature, 4D DSA frequently provided information that 2 experienced observers preferred over that provided by 2D or 3D studies. Although we did not explicitly ask whether the 4D dataset contained information equivalent to that in the combination of 2D and 3D series, we believe that this may be the case.…”
Section: Discussionmentioning
confidence: 99%
“…through the subject's vasculature at the frame rate of the rotational projection image acquisition (typically 30 frames/s). 1 Figure 2 shows an example of the contrast dynamics in the rotational projections along with a display of these dynamics as seen in the 4D reconstructions.…”
Section: Image Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4D-DSA has been shown to provide higher temporal and spatial resolution than current MR imaging/MRA and CT angiography. 16 In addition, 4D reconstructions allow examining the vasculature from any angle with any desired temporal point, which can facilitate the delineation of a nidus by judging the sequential appearance of different components of feeding arteries, nidi/fistulas, and draining veins of AVMs or DAVFs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to 2D-DSA, fully time-resolved 3D-DSA, also known as 4D-DSA, provides a series of time-resolved 3D volumes that correspond to contrast dynamics with a C-arm-based imaging system. 16 While the reconstruction of a 4D-DSA image from a single rotational image acquisition has some inherited technical difficulties, as mentioned by Royalty, 17 the volumetric vascular morphology and bolus-arrival patterns reconstructed from 4D-DSA algorithms are validated. 17 An animal study based on a canine model also demonstrated that 4D-DSA is capable of delineating vasculature effectively.…”
mentioning
confidence: 99%